M-DIN Application Strategy of Bank Muamalat KCP Kuningan in the Era of Bank Digitalization - Abdul Ghoni; Tria Lestari; Toto Suharto; Alvien Septian Haerisma (el-Jizya: Jurnal Ekonomi Islam, 2024)
In the era of digitalization, the banking sector undergoes significant transformation to meet the increasingly sophisticated and mobile demands of customers. Bank Muamalat, as a leading Islamic bank in Indonesia, is not exempt from the pressure to innovate and adapt to technological changes. This research employs a qualitative method with a case study approach at Bank Muamalat KCP Kuningan. Data is collected through interviews with internal bank informants and customers, as well as direct observations. The research findings indicate that the operational procedures of the M-DIN application at Bank Muamalat are proven to be simple and user-friendly, providing convenience from registration to the creation of Transaction Identification Numbers (TIN). The bank adopts a proactive strategy with innovative features, including aspects of Islamic principles and unique services, demonstrating awareness of technological innovation. Active education provided to customers by bank employees successfully increases user interest in M-DIN. The application is directed to every customer opening an account, resulting in a significant increase in M-DIN adoption by Bank Muamalat.